2022
DOI: 10.1186/s12864-022-08838-5
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two lineages: how the strains of the earliest divergent symbiotic Frankia clade spread over the world

Abstract: It is currently assumed that around 100 million years ago, the common ancestor to the Fabales, Fagales, Rosales and Cucurbitales in Gondwana, developed a root nodule symbiosis with a nitrogen-fixing bacterium. The symbiotic trait evolved first in Frankia cluster-2; thus, strains belonging to this cluster are the best extant representatives of this original symbiont. Most cluster-2 strains could not be cultured to date, except for Frankia coriariae, and therefore many aspects of the symbiosis are still elusive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 59 publications
(98 reference statements)
1
18
0
Order By: Relevance
“…Cluster 1 contains as-yet-uncultured Frankia microsymbionts, which are characterised by profuse sporulation within nodules tissues (Sp + types; Schwintzer, 1990 ), and a very higher proportion of cluster 2 strains are as-yet-uncultured. The Candidatus status has been used to accommodate some of these uncultured Frankia which were defined based on genome sequences ( Persson et al, 2011 , 2015 ; Nguyen et al, 2016 , 2019 ; Normand et al, 2017 ; Herrera-Belaroussi et al, 2020 ; Pozzi et al, 2020 ; Berckx et al, 2022 ). Two strains from cluster 2 have been successfully cultivated following a dual approach consisting of comparative genomics and direct physiological assay on nodule tissues ( Gtari et al, 2015 ; Gueddou et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1 contains as-yet-uncultured Frankia microsymbionts, which are characterised by profuse sporulation within nodules tissues (Sp + types; Schwintzer, 1990 ), and a very higher proportion of cluster 2 strains are as-yet-uncultured. The Candidatus status has been used to accommodate some of these uncultured Frankia which were defined based on genome sequences ( Persson et al, 2011 , 2015 ; Nguyen et al, 2016 , 2019 ; Normand et al, 2017 ; Herrera-Belaroussi et al, 2020 ; Pozzi et al, 2020 ; Berckx et al, 2022 ). Two strains from cluster 2 have been successfully cultivated following a dual approach consisting of comparative genomics and direct physiological assay on nodule tissues ( Gtari et al, 2015 ; Gueddou et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The association of each cluster with its group of host plants has been discussed in several publications (Benson and Dawson 2007 , Svistoonoff et al 2014 , Nguyen et al 2016 ). Frankia cluster-2 is the earliest divergent symbiotic clade within the genus (Nguyen et al 2016 , 2019 , Berckx et al 2022a ), and its host plants include Ceanothus (Rhamnaceae, Rosales), the Dryadoideae except for Dryas octopetala (Rosaceae, Rosales), Datiscaceae (Cucurbitales), and Coriariaceae (Cucurbitales).…”
Section: Introductionmentioning
confidence: 99%
“…Several more metagenome-assembled genomes (MAGs) of Frankia cluster-2 were sequenced from whole nodules obtained from both greenhouse cross-inoculation experiments and field samples. Here it was found that several closely related strains not only occupy a single nodule (Normand et al 2017 , Nguyen et al 2019 , Berckx et al 2022a ), but that some strains can persist as nodule-associated bacteria under unfavourable conditions and become the main symbiont in a more suitable host plant (Berckx et al 2022a ). Based on the analysis of the core genomes of Frankia cluster-2 strains from greenhouse samples, it could be concluded that the strains occurring in Eurasia, namely from France to Japan, form a single group with very low diversity (Nguyen et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations